Validation of hybrid URANS/LES methods for determination of forces and wake parameters of KVLCC2 tanker at manoeuvring conditions. Issue 2 (3rd May 2016) - Abbas, N.; Kornev, N.
Abstract : In this paper, computations of integral forces, surface pressure distribution and the wake behind the KVLCC2 tanker under simple manoeuvring (drift angles 6° and 12°) and complete manoeuvring (drift angle and yaw rate of 0.2, 0.4 and 0.6) conditions were performed and their results were compared with experimental results by Kume, K., Hasegawa, J., Tsukada, Y., Fujisawa, J., Fukasawa, R. and Hinatsu, M. (2006. Measurements of hydrodynamic forces, surface pressure, and wake for obliquely towed tanker model and uncertainty analysis for CFD validation. Journal of Marine Science and Technology, 11 (2), pp.65–75). Different numerical methods including URANS k- ω SST (Menter. 1993. Zonal two equation k- ω turbulence models for aerodynamic flows. AIAA Papers, 93–2906), the hybrid URANS-LES model proposed in Kornev, N., Taranov, A., Shchukin, E. and Kleinsorge, L. (2011. Development of hybrid urans-les methods for flow simulation in the ship stern area. Ocean Engineering, 38, pp.1831–1838), the hybrid Improved Delayed Detached Eddy Simulation approach (Shur, M. L., Spalart, P. R., Strelets, M. K., and Travin, A. K. 2008. A hybrid RANS-LES approach with delayed-DES and wall- modelled LES capabilities. International Journal of Heat and Fluid Flow, 29 (6), pp.1638–1649) based on Spalart-Allmaras URANS model were utilised. The doubled model of the KVLCC2 tanker with the scale (1/64.4) without appendages (propeller and rudder) was calculated at Reynolds number of 3.95 × 10 6 and Froude number of 0.142. The free surface deformation effect was neglected. Calculations were performed using OpenFOAM toolkit.